2012
DOI: 10.1016/j.jmbbm.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical behavior of superelastic Ti–24Nb–0.5O and Ti–24Nb–0.5N biomedical alloys

Abstract: To cite this version:A. Ramarolahy, Philippe Castany, F. Prima, P. Laheurte, Isabelle Péron, et al.. Microstructure and mechanical behavior of superelastic Ti-24Nb-0.5O and Ti-24Nb-0.5N biomedical alloys.Journal AbstractIn this study, the microstructure and the mechanical properties of two new biocompatible superelastic alloys, Ti-24Nb-0.5O and Ti-24Nb-0.5N (at.%), were investigated. Special attention was focused on the role of O and N addition on α ″ formation, supereleastic recovery and mechanical strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 22 publications
4
71
3
Order By: Relevance
“…This value of recovery strain revealed in our newly developed Ti-23Hf-3Mo-4Sn alloy is larger than that commonly observed values in binary solution treated Ti-Nb alloys [5,7,10]. Mechanical characteristics listed in Table. 1 also show that the specimen heat treated at 1073 K and 1173 K exhibited a σ CSS of about 620 and 640 MPa, respectively.…”
Section: Resultscontrasting
confidence: 50%
See 2 more Smart Citations
“…This value of recovery strain revealed in our newly developed Ti-23Hf-3Mo-4Sn alloy is larger than that commonly observed values in binary solution treated Ti-Nb alloys [5,7,10]. Mechanical characteristics listed in Table. 1 also show that the specimen heat treated at 1073 K and 1173 K exhibited a σ CSS of about 620 and 640 MPa, respectively.…”
Section: Resultscontrasting
confidence: 50%
“…In addition, for the sake of comparison, the mechanical characteristics of commercially pure CP-Ti (grade 2), Ti-6Al-4V (grade 5 ELI) and binary Ti-Nb alloys [7,10] are also presented in Table. 1. In the present study, the critical stress for slip, σ CSS , is defined as the stress at which 0.5% of plastic deformation, ε p , is induced during the cycling tensile test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works, different kinds of thermo-mechanical treatments were used for the processing of the alloy (cold deformation, hot rolling and warm rolling) [1][2][3][4][5][6]. Thanks to these investigations, a superelasticity of about 3.3% was obtained [3][4][5][6], which is much higher than the values usually obtained with binary Ti-Nb alloys [7][8][9]. Moreover, " flash treatments "…”
Section: Introductionmentioning
confidence: 96%
“…Depending on the type of thermomechanical treatment they have undergone, TiNb alloys, with a composition ranging from Ti-23Nb to Ti-26Nb, can have varying Young's modulus. Recently, we have demonstrated that severe cold rolling deformation followed by flash aging treatment on TiNb and TiNbZr, in order to produce ultra fine grains and/or omega phase, is more effective to improve strength [26][27][28][29][30]. High ultimate tensile strength (800 MPa), and low modulus (30 GPa) are obtained by nanostructuration process, as illustrated in Fig.…”
Section: Research Agency Through the Functional Materials And Innovatmentioning
confidence: 99%